Relationship between age, gender, BMI, comorbidity and AEFI Variables with S-RBD antibody levels post covid-19 vaccination - Mimanda, Yona; Muniroh, Muniroh; Sari, Nurmila (Science Midwifery, 2024)
The coronavirus disease 2019 (COVID-19) pandemic is a global problem caused by the SARS CoV-2 virus. Covid-19 vaccination, which is believed to be a solution, started after almost a year of the pandemic. The vaccination program in Indonesia initially used the Sinovac vaccine, a vaccine made from killed or inactivated viruses. This platform has been used in making vaccines for a long time. Vaccination at the UIN Syarif Hidayatullah Jakarta campus uses a vaccine made by PT Bio Farma, COVID-19 Vaccine, with the same raw materials as Sinovac. Cross-sectional research and research subjects were 53 lecturers and teaching staff who had received 2 doses of the COVID-19 Vaccine. Characteristics of age, gender, body mass index, comorbidities and adverse events after immunization (AEFI) were obtained from interviews, questionnaires and physical examination. It was found that there were no significant differences in S-RBD IgG antibody levels in young and elderly adults (p=0.85), male and female groups (p=0.74), groups with comorbidities (p=0.93), history of AEFI (p=0.78). However, there was a significant difference between normal BMI and abnormal BMI (p=0.03). The variable that had a significantly different relationship in this study was the mean level of IgG S-RBD antibodies in the overweight and obese groups with normal weight.